2017
DOI: 10.3389/fphys.2017.00342
|View full text |Cite
|
Sign up to set email alerts
|

Icariin, a Novel Blocker of Sodium and Calcium Channels, Eliminates Early and Delayed Afterdepolarizations, As Well As Triggered Activity, in Rabbit Cardiomyocytes

Abstract: Icariin, a flavonoid monomer from Herba Epimedii, has confirmed pharmacological and biological effects. However, its effects on arrhythmias and cardiac electrophysiology remain unclear. Here we investigate the effects of icariin on ion currents and action potentials (APs) in the rabbit myocardium. Furthermore, the effects of icariin on aconitine-induced arrhythmias were assessed in whole rabbits. Ion currents and APs were recorded in voltage-clamp and current-clamp mode in rabbit left ventricular myocytes (LVM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…According to our previous literature, the recording of the I Ca.L was started 10 min after the whole-cell mode was established and the entire experimental record was finished in 20 min to eliminate the deviation induced by I Ca.L rundown ( Jiang et al, 2017 ). By studying the effects of Cur on the I – V relationships, steady-state (in)activation, and time-dependent recovery of I Ca.L in ventricular myocytes, the results showed that Cur inhibited I Ca.L in a concentration-dependent manner ( Figure 2A ) and the maximum current density of I Ca.L was obtained at the test potential of 5 mV ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…According to our previous literature, the recording of the I Ca.L was started 10 min after the whole-cell mode was established and the entire experimental record was finished in 20 min to eliminate the deviation induced by I Ca.L rundown ( Jiang et al, 2017 ). By studying the effects of Cur on the I – V relationships, steady-state (in)activation, and time-dependent recovery of I Ca.L in ventricular myocytes, the results showed that Cur inhibited I Ca.L in a concentration-dependent manner ( Figure 2A ) and the maximum current density of I Ca.L was obtained at the test potential of 5 mV ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…135 As a calcium channel blocker, icariin may abrogate this effect. 136,137 The results of the network pharmacology analysis suggested that icariin has therapeutic potential for the treatment of ischemic stroke (Supplementary Table S1). Disruption of the BBB plays a key role in the progression and exacerbation of brain injury following stroke.…”
Section: Ischemic Strokementioning
confidence: 99%
“…In several experimental animal models it has been shown that Ica treatment improves isoproterenol-induced cardiac dysfunction and remodeling [44], exerts an antiantiarrhythmic effect [46], reduces infarct size after myocardial ischemia-reperfusion (I/R) injury [47,48], and prevents pro-inflammatory pathway activation and ROS production in isoproterenol-induced takotsubo rat models [49].…”
Section: Introductionmentioning
confidence: 99%